9m-5-3m=

Simple and best practice solution for 9m-5-3m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-5-3m= equation:


Simplifying
9m + -5 + -3m = 0

Reorder the terms:
-5 + 9m + -3m = 0

Combine like terms: 9m + -3m = 6m
-5 + 6m = 0

Solving
-5 + 6m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 6m = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 6m = 0 + 5
6m = 0 + 5

Combine like terms: 0 + 5 = 5
6m = 5

Divide each side by '6'.
m = 0.8333333333

Simplifying
m = 0.8333333333

See similar equations:

| 2y-20+y+y+2y-20=720 | | 17n+22=80 | | (2x)(2x)-5x=3000 | | 9u=49+2u | | y^2-6y=-91 | | 5x+3x+20=140 | | 9m-5-2m= | | 8+18n= | | 3y+y-16=145 | | 8n+4=-52 | | Y-16+3y=145 | | -6(y+7)=-3y-45 | | 4y+14=13-y | | (3z-2)2-8(3z-2)=20 | | M(n-7)= | | -2u+46=-6(u-7) | | T(t+9)= | | An=(n-1)2+3 | | (x^2-y^2)*dy-x*y*dx=0 | | 4(2f-1)= | | 2(u+9)=-8u-32 | | -8u-21=-3(u+2) | | 3(2x+1)=144 | | 11x-4x+132=11x+48 | | 2x^2+10x-2475=0 | | X*X-45*X+324=0 | | 5s-9+4s=28.5 | | 25*cos^2*x-9=0 | | 14u=35+9u | | 25(cos^2)x-9=0 | | -8.5(5+6a)=-26.5 | | 43-8x=19+4x |

Equations solver categories